Algoritmi, strutture e agire sociale - Pronzato, Riccardo (FrancoAngeli, 2024)
This book examines the everyday relationships with algorithmic media at the sociological level, taking into consideration both structural and social actor-related dimensions. Specifically, drawing on a critical review of multiple theoretical contributions and the analysis of two empirical cases involving university students and healthcare professionals, it discusses how algorithmic media exert hegemonic power in contemporary society. Within this power, however, it is highlighted a dialectical, symbiotic, and fluid relationship between structure and agency, in which the structures activated and reproduced by algorithmic media can become spaces of action and reflection for users. In the conclusions, it is argued that sociology itself can offer tools to facilitate a critical understanding of technologies and the development of activities that can counter the hegemonic power of platforms.